PERSEPSI MASYARAKAT TERHADAP PARTAI POLITIK BARU PADA PEMILU 2019 DI KELURAHAN MAMBORO BARAT KOTA PALU - Irwansyah Kamindang; Moh. Tabran Hi. Ambotuo; Nurhayaty Hamid (Journal Publicuho, 2022)
This study aimed to determine the Mamboro Village community's perception of the New Political Party in the 2019 legislative election. The method used in this research is descriptive qualitative where interviews and documentation as instruments to collect data. This study aims to determine the political perception of the people in the West Mamboro sub-district towards the new political parties in the 2019 legislative elections. The results show that the political perception (political attitude) of the people of the West Mamboro sub-district towards the presence of new political parties, both from the level of introduction of political parties, the level of the introduction of political party candidates, the level of introduction to political party programs, and the level of knowledge and media introducing these new political parties is very low. This political attitude (political perception) will greatly influence the political preferences of the people in the West Mamboro Village, whose socio-political structure is more likely to be influenced by factors in the social environment where they live. Parents, husbands, mothers and families have a very strong influence in determining political preferences in the 2019 election. Thus, the tendency of West Mamboro people's political preferences towards political parties, one of which is strongly influenced by the acceptability of political figures or figures who are considered to have strong social ties ( sociological approach) with most of the people of West Mamboro.